Analysis of bioactive compounds for Jasmine flower via Gas chromatography-mass spectrometry (GC-MS) - Rassem, Hesham H. A.; Nour, A. H.; R. M., Yunus (Penerbit UTM Press, 2018)
The current work analyses the chemical constituents of Jasmine flower using Chromatography-Mass Spectrometry (GC-MS). The dried Jasmine flower powder was extracted by methanol via the Microwave-assisted Hydrodistillation (MAHD) process. The GC-MS analysis revealed different peaks that showed the presence of ten compounds. In the current study, we have focused on the main compounds that can be used for biological activity, i.e. 2-Phenylthiolane (57.31%), Cyclohexene, 3-ethenyl- (25.91%), Acetaldehyde (12.70%), N-Methylallylamine (9.99%), Propanamide (6.79%) and Phthalic acid, bis (7-methyloctyl) ester (5.21%). The bio-compounds with methanol extract of Jasmine flower were analyzed by using GC-MS. Functional group analysis was carried out on the volatile oil obtained through MAHD by using Fourier Transform Infrared Spectroscopy (FTIR). The surface morphologies of untreated dried powdered Jasmine flower (i.e. raw powdered jasmine flower without soaking into methanol solution prior to extraction) and pre-treated powdered Jasmine flower (soaked into methanol solution for 1 hr) were investigated through SEM analysis.